Corroboration of cross-reactivity between Mycobacterium leprae and hosts’ salivary and cutaneous proteins: A hope for prognostic biomarkers for the pathogenesis of reactions in leprosy - Pathak, Vinay Kumar; Singh, Itu; Singh, Shoor Vir; Sengupta, Utpal (Frontiers in Microbiology, 2022)
Immunological reactions are frequent complications that may occur either before, during, or after treatment and affect 30–50% of leprosy patients. The presence of autoantibodies like rheumatoid factor, antinuclear factor, and antibodies to host collagen, keratin, actin, myosin, endothelial cells, and myelin basic protein (MBP) has been earlier reported in leprosy patients. The purpose of this study was to identify cross-reactive proteins in clinical samples such as saliva and slit skin scrapings (SSS) of leprosy patients which could be utilised as prognostic biomarkers for Type 1 Reaction (T1R) in leprosy. A total of 10 leprosy patients in T1R and 5 healthy volunteers were recruited. The protein was extracted from their SSS and saliva samples, thereafter, isoelectric focusing (IEF) and two-dimensional PAGE were performed to analyse the proteins. Furthermore, the cross-reactivity was identified by western blotting host proteins in gel against purified IgG from Mycobacterium leprae soluble antigen (MLSA)- hyperimmunized rabbit sera, thereafter, cross-reactive proteins were identified by MS/MS. The cross-reactive host proteins were analysed for homologous bacterial proteins and B cell epitopes (BCEs) were predicted by using bioinformatic tools. A total of five spots of salivary proteins namely S100-A9, 35.3 kDa, and 41.5 kDa proteins, Serpin peptidase inhibitor (clade A), Cystatin SA-III, and four spots of SSS namely 41.4 kDa protein, Alpha-1 antitrypsin, vimentin, and keratin 1, were identified as cross-reactive. Further, a total of 21 B cell epitopes (BCEs) of cross-reactive host proteins were predicted and visualised. This data provides strong evidence of cross-reactivity/ molecular mimicry between host and pathogen in leprosy patients with reaction. These BCEs of cross-reactive proteins could be further studied to predict reactions and may be utilised as an early diagnostic biomarker for T1R in leprosy.